Kearifan Lokal Pesantren sebagai Bangunan Ideal Moderasi Islam Masyarakat Madura - Zainuddin Syarif; Abd Hannan (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2020)
In many social studies, Madura is known as an archipelago with its various local wisdom, embodied in the socio-religious systems and structures of pesantren. Pesantren is a social system and structure that contains local values which have great influence especially on the formation of Islamic traditions among the Madurese community. This study employs a qualitative approach with a library method, combined with the perspective of the sociology of religion. Theoretically, this study is aimed to enrich the scholarship on social and religious studies, and practically to build Islamic culture that upholds the values of moderatism. The findings of this study contain an in-depth description of local wisdom values of pesantren in Madura, their role in, and influence on, the formation of Islamic moderatism among the Madurese community.